The Influence of Electronic Word Of Mouth on Gen Z's Purchase Intention on Shopee Social Commerce Platform - Ananda Ramadhan, Syahfara; Hartono, Arif (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of electronic word of mouth on gen Z buying interest on the social commerce platform Shopee. The approach used in this study is a quantitative approach. Data collection techniques by distributing online questionnaires to 200 respondents using Google Form. The sampling technique uses a non-probability sampling technique using the purposive sampling method and then processed using structural equation modeling SEM (Structural Equation Modeling) using the PLS program. This study found that perceived informativeness, perceived persuasiveness, source expertise, source trustworthiness have a positive and significant effect on E-WOM Usefulness, in addition perceived persuasiveness, source expertise, source trustworthiness have a positive and significant effect on E-WOM Credibility. This study also found that E-WOM Usefull and E-WOM Credibility have a positive and significant effect on Purchase Intention.